The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1246/cl.220016
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of an Electrochemical Oxidative Peak of Gold/Bis(trifluoromethylsulfonyl)amide-based Ionic Liquid Interfaces at Elevated Temperatures

Abstract: The electrochemical behavior of a Au(111) electrode was investigated in three ionic liquids (ILs) containing trifluoromethylsulfonyl-based anions at temperatures ranging from 20 °C to 100 °C. Gold oxidation, that is, gold etching, occurred at elevated temperatures (≥70 °C) and was found to be dependent on the chemical structure of the ILs. These results allow us to simplify the procedure of gold dissolution in bis(trifluoromethylsulfonyl)amide-based ILs, thereby improving the efficiency of electrochemical etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…81 We found that Au can be oxidized in [Tf 2 N] ¹ -based ILs at high temperatures (²70 °C). 82 The temperature change of ILs promotes the elution of gold complexes even in the absence of specific adsorption of halide ions. These are fundamental studies, but we could elucidate only one aspect of the surface electrochemistry of ILs.…”
Section: ¹mentioning
confidence: 99%
“…81 We found that Au can be oxidized in [Tf 2 N] ¹ -based ILs at high temperatures (²70 °C). 82 The temperature change of ILs promotes the elution of gold complexes even in the absence of specific adsorption of halide ions. These are fundamental studies, but we could elucidate only one aspect of the surface electrochemistry of ILs.…”
Section: ¹mentioning
confidence: 99%